MEMBANGUNKOMUNIKASI AVITALK BERBASIS ANDROID DENGAN MEMANFAATKAN FREKUENSI 2.4 Ghz PADA JARINGAN LOCAL AREA NETWORK (LAN) - Galih Andita Sukma; Haruno Sajati; Hero Wintolo (Compiler, 2016)
The importance of communication increases development of information and communication technology in world so rapidly, especially in telecommunications equipment. Mobile phone or smartphone is one type of communication tools that provide communication services to a wide range of features offered but the services offered are not free. AviTalk is applications and services to communicate for free with the use of smartphones based on Android and has a wifi enable this feature. This communication utilizing wifi network at a frequency of 2.4 GHz as to communication network. Test the application is done by trying on some of the features on a smartphone application with different specifications. From the test produced a smartphone that can run the application properly in some smartphones with Android operating system version 4.2 and above, and the smartphone is connected to a wifi network.